Microbiota instruct IL-17A-producing innate lymphoid cells to promote skin inflammation in cutaneous leishmaniasis - Tej Pratap Singh (Public Library of Science (PLoS), 2021)
Innate lymphoid cells (ILCs) comprise a heterogeneous population of immune cells that maintain barrier function and can initiate a protective or pathological immune response upon infection. Here we show the involvement of IL-17A-producing ILCs in microbiota-driven immunopathology in cutaneous leishmaniasis. IL-17A-producing ILCs were RORγt+ and were enriched in Leishmania major infected skin, and topical colonization with Staphylococcus epidermidis before L. major infection exacerbated the skin inflammatory responses and IL-17A-producing RORγt+ ILC accumulation without impacting type 1 immune responses. IL-17A responses in ILCs were directed by Batf3 dependent CD103+ dendritic cells and IL-23. Moreover, experiments using Rag1-/- mice established that IL-17A+ ILCs were sufficient in driving the inflammatory responses as depletion of ILCs or neutralization of IL-17A diminished the microbiota mediated immunopathology. Taken together, this study indicates that the skin microbiota promotes RORγt+ IL-17A-producing ILCs, which augment the skin inflammation in cutaneous leishmaniasis. Author summary Cutaneous leishmaniasis includes a spectrum of diseases ranging from a single ulcerative lesion to severe metastatic lesions, and the magnitude of the disease is often influenced by factors that are independent from the parasite burden. Here, using L. major infected mice, we discovered that microbiota-dependent IL-17A–secreting ILCs promote increased disease early after infection. While the microbiota driven IL-17A–secreting ILCs mediated inflammatory response was independent of the parasite burden and a type 1 immune responses, it required stimulation of Batf3-dependent skin dendritic cells, production of IL-23 and the presence of neutrophils. This study provides mechanistic insight into how microbiota and the innate immune system influence pathology early after infection with L. major.